DEXAMETHASONE IMPLANT FOR DIABETIC MACULAR EDEMA IN NAIVE COMPARED WITH REFRACTORY EYES: The International Retina Group Real-Life 24-Month Multicenter Study. The IRGREL-DEX Study - Matias Iglicki (2019)
PURPOSE: To investigate efficacy and safety of repeated dexamethasone (DEX) implants over 24 months, in diabetic macular edema (DME) eyes that were treatment naive compared with eyes refractory to anti-vascular endothelial growth factor treatment, in a real-life environment. METHODS: This multicenter international retrospective study assessed best-corrected visual acuity and central subfield thickness (CST) of naive and refractory eyes to anti-vascular endothelial growth factor injections treated with dexamethasone implants. Safety data (intraocular pressure rise and cataract surgery) were recorded. RESULTS: A total of 130 eyes from 125 patients were included. Baseline best-corrected visual acuity and CST were similar for naive (n = 71) and refractory eyes (n = 59). Both groups improved significantly in vision after 24 months (P < 0.001). However, naive eyes gained statistically significantly more vision than refractory eyes (+11.3 ± 10.0 vs. 7.3 ± 2.7 letters, P = 0.01) and were more likely to gain ≥10 letters (OR 3.31, 95% CI 1.19-9.24, P = 0.02). At 6, 12, and 24 months, CST was significantly decreased compared with baseline in both naive and refractory eyes; however, CST was higher in refractory eyes than in naive eyes (CST 279 ± 61 vs. 313 ± 125 μm, P = 0.10). CONCLUSION: Over a follow-up of 24 months, vision improved in diabetic macular edema eyes after treatment with dexamethasone implants, both in eyes that were treatment naive and eyes refractory to anti-vascular endothelial growth factor treatment; however, improvement was greater in naive eyes.